The United States and the rise, fall and future prospects of the (Comprehensive and Progressive Agreement for) Trans-Pacific Partnership - Ji, Xianbai (2019)
The Trans-Pacific Partnership (TPP) is one of the most politically resilient economic arrangements in the past decade. Its evolution including highs and lows is closely tied to the shifting positions of the United States (U.S.). This article examines the role played by the U.S. behind the rise, fall and future of the TPP and its successor, the Comprehensive and Progressive Agreement for TPP (CPTPP). This article first revisits Washington’s three-fold geo-economic interest behind the original TPP in terms of projecting influence in Asian affairs, supporting Obama’s Rebalance to Asia strategy and leading the regional rule-writing efforts to facilitate 21st century trade and investment. This article then delves into offering an explanation of the loss of the TPP in the U.S. It argues that the TPP was crippled under an overlay of bad timing, bad politics and bad context. Specifically, the 2016 elections, Trump’s disapproving views on the TPP and the narrow, underperforming US trade policy ecosystem at large were the key factors leading to the US withdrawal from the TPP. Lastly, the article ponders upon the future of the CPTPP by asking and answering three questions: Will China and other countries join the bloc? Will the CPTPP evolve into a Free Trade Area of the Asia-Pacific? Are the CPTPP and the China-backed Regional Comprehensive Economic Partnership part of the Asia-Pacific’s constructive response to Trump protectionism?